IPortal: the swiss grid proteomics portal: Requirements and new features based on experience and usability considerations. (13th May 2014) - Kunszt, Peter; Blum, Lorenz; Hullár, Béla; Schmid, Emanuel; Srebniak, Adam; Wolski, Witold; Rinn, Bernd; Elmer, Franz‐Josef; Ramakrishnan, Chandrasekhar; Quandt, Andreas; Malmström, Lars; Wilkins‐Diehr, Nancy; et al.
Summary Development of workflow and data management systems are challenging because of the need to provide a service for users with varying degrees of expertise from novices to experts with more knowledge than the developers. We have received feedback from users and developers on the functionality and usability of the Swiss Grid Proteomics Portal, now called iPortal, during its first year of operation. Monitoring and interaction with the production system under heavy use have provided further information on how to improve efficiency and stability. In a second, highly upgraded version of iPortal, we have introduced several new concepts based on this feedback. In this paper, we detail the requirements and the improvements we have made, and also give an outlook on future directions. Copyright © 2014 John Wiley & Sons, Ltd.